Modern financial statements too complicated to managers and laymen: A critical survey - J. M. Language (South African Journal of Business Management, 1985)
This article is an attempt at scrutinizing accounting practice in South Africa. Firstly, the author demonstrates that the Company Law in South Africa is fairly vague regarding the format and formulation of financial statements. Questions regarding the general use of terms, and more specifically 'generally accepted practice', are raised. Finally, the author discusses some unacceptable aspects of recent presentation of accounting statements.
Keywords: 650